Integration of Islam and Science in Indonesia: A Comparative Analysis of the Epistemological Perspectives of Mulyadhi Kartanegara, Amin Abdullah, and Imam Suprayogo - Aan Rukmana; Nuruddin Al Akbar (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Discourse on the relationship between Islam and science in Indonesia has grown substantially. However, the epistemological positions of its leading proponents have rarely been compared side by side, leaving a gap in understanding how their models converge and diverge and what these similarities and differences mean for Islamic higher education. Objective: This study compares Mulyadhi Kartanegara’s, Amin Abdullah’s, and Imam Suprayogo’s epistemological perspectives on the integration of Islam and science and examines the implications of their integrative models for the development of Islamic higher education in Indonesia. Methods: This qualitative library study employs a philosophical approach and uses critical-analytical and comparative methods. Primary texts written by the three scholars were coded according to ontological, epistemological, and axiological categories. The findings were then triangulated with secondary literature to enhance the credibility of the interpretations. Results: Although the three scholars differ in terminology and emphasis, their perspectives converge on integration as the model that most comprehensively unifies religious and modern sciences within a single, mutually reinforcing epistemic framework. Conclusion: This study affirms integration as the most viable model for advancing Islamic scholarship in Indonesia and provides a comparative framework for future research on Islamic epistemology and higher education curricula.